Pentigraf Bahan Ajar Untuk Meningkatkan Kreativitas Menulis Siswa Sekolah Menengah Pertama Di Lokasi Pariwisata Kawasan Teluk Tomini - Agriyanti Mestari, sri; el Walidayni Kau, Magvirah; Rusnarti Usu, Novi (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
The goal to be achieved in this service activity is to increase student creativity in writing short stories through the use of 'Pentigraph' as teaching material by involving experience and the surrounding environment as a theme for writing paragraphs. This can provide valuable benefits for students who are in the coastal tourism area. Through learning creative writing about tourism and one's own culture can help strengthen cultural identity and increase pride in the cultural heritage. In addition, writing about cultural sites, traditional events, and other cultural heritage can stimulate interest in research and advocacy, enabling students to become conscious change agents committed to cultural sustainability and promoting responsible tourism practices in coastal tourism areas that not only help the local economy but also raise global awareness about the importance of cultural preservation. The target participants of this activity are the surrounding community, namely adolescents and children located at the State Junior High School No. 1 Kabila Bone District, Bone Bolango Regency. This service activity will be carried out only for 1 meeting with a duration of 90 minutes. With this service activity, it is hoped that it will be able to help the tourism area community to be able to manage the tourism area and be able to serve visitors both local and foreign well.